2009
DOI: 10.1086/596061
|View full text |Cite
|
Sign up to set email alerts
|

Functional IL‐10 Gene Polymorphism Is Associated with Chagas Disease Cardiomyopathy

Abstract: This study was designed to determine whether the functional IL-10 gene polymorphism -1082G/A is associated with the development of cardiomyopathy in individuals infected with Trypanosoma cruzi and whether interleukin (IL)-10 expression can be correlated with patients' cardiac function. Our results demonstrated that the polymorphic allele, which correlates with lower expression of IL-10, was associated with the development of Chagas disease cardiomyopathy. Accordingly, correlative analysis showed that low IL-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 16 publications
5
87
1
2
Order By: Relevance
“…However, genetic susceptibility to T. cruzi infection and the development of cardiomyopathy is complex and heterogeneous and likely involves several genes, each with a modest contribution on the pathogenesis of the disease. In fact, genetic studies in human beings have addressed the relation between cytokine and chemokine gene polymorphisms and development of chagasic heart disease [16][17][18][19][20][21][22]. In this study, we investigated the possible association of CCL5/RANTES and CXCL8/interleukin 8 (IL-8) chemokines, and CCR2 and CCR5 chemokines receptors cluster gene polymorphisms with the development of chagasic cardiomyopathy in a case-control study in Colombia endemic area.…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic susceptibility to T. cruzi infection and the development of cardiomyopathy is complex and heterogeneous and likely involves several genes, each with a modest contribution on the pathogenesis of the disease. In fact, genetic studies in human beings have addressed the relation between cytokine and chemokine gene polymorphisms and development of chagasic heart disease [16][17][18][19][20][21][22]. In this study, we investigated the possible association of CCL5/RANTES and CXCL8/interleukin 8 (IL-8) chemokines, and CCR2 and CCR5 chemokines receptors cluster gene polymorphisms with the development of chagasic cardiomyopathy in a case-control study in Colombia endemic area.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experimental studies also show that administration of recombinant IL-10 reverses or alleviates symptoms of many adverse pregnancy outcomes [45][46][47][48]. Polymorphic change in the human IL-10 gene promoter are thought to contribute to reduced IL-10 production and to the onset and severity of autoimmune, neoplastic, and infectious disorders such as systemic lupus erythematosus and Alzheimer's disease [49][50][51]. Evidence has also been found for the associated of the IL-10 gene promoter polymorphisms with other adverse pregnancy outcomes [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, exposure of lymphocytes to T. cruzi-infected monocytes led to an increase in surface expression of CTL4 by T cells from IND, but not CARD, patients compared to normal control individuals. As will be discussed, Costa et al (2009) have recently demonstrated an association between a functional IL-10 gene polymorphism (-1082G/A), which leads to lower expression levels of IL-10, and the worsening of cardiac function in chronic Chagas disease. Hence, it is conceivable that IL-10-secreting cells are underrepresented in the monocyte-depleted populations of PBMCs that Albareda et al (2006) have used to measure memory T cell responses elicited by Brazil strain-infected DCs.…”
Section: ) According To This Study Cd8mentioning
confidence: 95%
“…The observation that monocytes derived from chronic chagasic patients showed upregulated secretion of IL-10, further validated by the recent work of Souza et al (2007), supports the concept that IL-10 might counterbalance T H 1-induced immunopathology in the hearts of IND patients. As already mentioned, the severity of cardiac function abnormalities in Chagas disease (Costa et al 2009) was recently linked to the 1082G/A polymorphism of the IL-10 promoter (Turner et al 1997a, b), of which the phenotype is low IL-10 production. In a recent study, Araujo et al (2007) Admittedly, additional studies are required to substantiate the hypothesis that pathogenic T H 1 clones might contribute to the development of chronic myocardiopathy.…”
Section: Cohort Studies Using Epi-ag Link T H 1 Responses To Severitymentioning
confidence: 99%